Kajian kinerja manajemen konstruksi dalam proyek pembangunan Water Treatment Plant (WTP) 300 LPD Simoro Sulawesi Tengah - Borahima, Adhim; Musa, Ratna; Watono, Watono (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The construction of the Simoro Water Treatment Plant (WTP) in Gumbasa District, Sigi Regency, Central Sulawesi, is a complex project aimed at improving regional infrastructure. This research aims to analyze the construction management of the project by applying the Critical Path Method (CPM) and Time Cost Trade Off (TCTO) methods to enhance time and cost efficiency. The CPM method is used to identify the project’s critical path and manage activities that most affect the total project duration. Meanwhile, TCTO is analyzed to optimize the additional costs needed to accelerate project completion without compromising the quality of the final results. The research results indicate that: (1) using the CPM method and Primavera software, the activities on the critical path include Start (Preparation), Cleaning and leveling work, Earth excavation work, Aggregate Base Layer B work, Earth excavation work, Aggregate Base Layer B work, Cut and Fill work, Bore Pile work (Reservoir), Earthwork (Reservoir), Pile Cap Foundation work (Reservoir), Concrete Floor work, Reservoir Tank work, Bore Pile Foundation work for Clearwell, Bore Pile Foundation work for IPA Building, Earthwork for IPA Building, Structure work for Coagulation Building, Structure work for Flocculation Building, Structure work for Sedimentation Building, Mechanical work, Electrical work, Scada Instrument, and Commissioning Test. (2) From the application of Time Cost Trade Off (TCTO) analysis, the lowest implementation cost obtained is Rp. 78,262,088,288.34 with the Crash condition of the implementation time being 913 days. This research provides significant contributions to improving construction management performance, particularly in terms of time and cost efficiency, and offers practical guidance for project managers in developing better and more effective project management strategies.